Embodying the virtual: resisting essentialising narratives in Northern Ireland. Issue 2 (4th May 2019) - Graffin, Lauren
Abstract: This article examines the use of a walking app, Belfast Bred in the Belfast City space. This app was developed by Kabosh and The Design Zoo in association with the Northern Ireland Tourist Board (NITB) and Belfast City Council and is led by Barney an Edwardian chef from the ill-fated Titanic. The article argues that the app itself is designed to contain the Belfast city space. Northern Ireland is being re-spatialised and branded as a 'Post-Conflict' society. The Northern Ireland Executive and the NITB are implementing a place branding agenda, which intends to promote the region to external investors and tourists. Belfast has seen a rise of gentrified spaces which complement the branding agenda in Northern Ireland and it is these sites that the app chooses to map, rather than the territorialised working-class residential areas in the city. This article will argue that although the app is designed to contain the branded Belfast space, its mode of delivery makes containment impossible. The interaction between virtual and actual frames frustrates this containment. The Belfast Bred app demonstrates that the space designed is rarely the space experienced as the user can control their own journey and build their own Brand Belfast.